SOSIALISASI PENGGUNAAN DAUN KELOR UNTUK PENCEGAHAN STUNTING DI DESA JANTI TULANGAN SIDOARJO - Arida Azka Nurina Ichwan; Syaifu Umar Achmadi; Elpi Nainggolan; Nur Sayidah; Jhosua Soputra; Moch Sabdan Adji Syahputra; Andriani, Vivin (Asawika : Media Sosialisasi Abdimas Widya Karya, 2025)
Stunting is a chronic nutritional problem that threatens the quality of future generations. One of the efforts to prevent stunting is through the use of local foods that are rich in nutrients, such as moringa leaves. This study used qualitative methods to explore the effectiveness of socialising the use of moringa leaves in increasing the knowledge of the community in Janti Village, Tulangan, Sidoarjo. Data was collected through educational sessions, demonstrations of moringa leaf processing, and interactive discussions with participants. The results of the socialisation activities indicate that these initiatives have successfully enhanced the community's understanding of the nutritional content of moringa leaves and their role in preventing stunting. Awareness of the importance of balanced nutrition through the consumption of moringa leaves is expected to contribute to the development of a healthy and high-quality future generation. Thus, the socialisation of moringa leaf usage emerges as a crucial strategy in stunting prevention efforts.